Devolatilization process of high-melt-index and high-transparency lithium polymer glue solution
The combined falling film evaporation and twin-screw extrusion process effectively addresses the challenges of wet devolatilization by producing transparent polymer pellets with low volatile content, enhancing operational efficiency and reducing environmental impact.
Patent Information
- Application Number
- CN202310750996.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-25
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2043-06-25
AI Technical Summary
Existing wet devolatilization technologies for lithium-based polymers face issues such as large equipment footprint, high energy consumption, opacity, equipment clogging, wastewater generation, and difficulty in achieving high transparency due to residual water, which are not addressed by traditional methods like solution polymerization or dry devolatilization.
A combined process using a falling film evaporation tower for pre-concentration and a twin-screw extruder for deep devolatilization, involving a multi-layer sieve structure and controlled evaporation and condensation, followed by underwater pelletizing and centrifugal dehydration to achieve high transparency and low volatile content.
The process achieves transparent polymer pellets with volatile content below 0.5%, reducing equipment complexity, energy consumption, and environmental impact, while enabling efficient solvent recovery and easy downstream processing.
Smart Images

Figure CN119192433A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a polymer glue post-processing method, in particular to a dry devolatilization process of a high melt index and high transparency lithium polymer glue, belonging to the technical field of rubber elastic material preparation. Background Art
[0002] There are three methods for producing synthetic rubber: suspension emulsion polymerization, gas phase polymerization and solution polymerization. Solution polymerization is the leading process technology for rubber production in the world. In the preparation of traditional lithium-based solution copolymerized styrene-conjugated diene elastomers SBC such as SBS, SIS, SEBS, SEPS and EPDM, water vapor condensation is usually used to remove the solvent from the polymer, commonly known as "wet devolatilization". At present, there are also commercially available styrene-butadiene copolymer transparent resins (KR-01 and KR03) that use heated screws to remove volatile solvents and granulate (commonly known as dry devolatilization).
[0003] The existing lithium polymers are devolatilized by wet method. The solvent, cyclohexane and water vapor are condensed together in the condensation kettle at 98-100℃. The recovered solvent must be refined and dehydrated to a water content of <20mg / Kg before it can be recycled. That is, it is necessary to add condensation, solvent recovery and refining, condensation gel extrusion dehydration, oven drying and other post-processing equipment. For molecular weight <8×10 4 , polymer rubber with a melt index higher than 12g / 10min will produce glue, agglomeration and blockage in the coagulation kettle, conveying machinery, pipelines, drying ovens and frying pans. In addition, wet devolatilization cannot meet the requirements of transparent polymers. Because organic high molecular polymers have barrier properties, the trace water remaining in the polymer is difficult to remove by drying, resulting in reduced transparency. In general, the wet devolatilization of anionic styrene-diene polymers has many equipment, long process flow, large floor space, poor operating site environment, wastewater generation, high energy consumption and large investment.
[0004] In the prior art ("Study on Wet Devolatilization Process of Ethylene Propylene Rubber", 2010, Chemical Technology), ethylene propylene rubber (J-2070) glue liquid was used for water vapor condensation and extrusion devolatilization. The w (total volatile matter) of the extruded sample was <0.5%; within the range of extruder speed of 50-120r / min, the extruded sample did not degrade, indicating that the devolatilization process is feasible and meets the requirements of ethylene propylene rubber devolatilization. Chinese patent (CN108840979A) discloses a SEPS elastomer and a preparation method thereof. The method uses a basic glue liquid before hydrogenation reaction of polystyrene polyisoprene polyethylene block copolymer, flashes and concentrates, and directly dry devolatilizes to obtain a SEPS elastomer. The SEPS elastomer prepared by the preparation method is obtained.
[0005] In recent years, with the development of economy, the demand for high melt index and high transparency resin materials has increased. Traditional transparent resins including polystyrene, polymethyl methacrylate, polycarbonate, styrene-acrylonitrile resin, K resin, EPDM rubber, polyolefin elastomer and high melt index and high transparency polystyrene-diene elastomer (SBC) are not suitable for wet devolatiles. In particular, elastic materials and process technologies of high melt index and high transparency anionic polymerized polystyrene-diene elastomers such as SBS, SIS and hydrogenated SEBS are proprietary technologies of major manufacturers. Summary of the invention
[0006] In view of the defects of the prior art of wet devolatilization technology for polystyrene-diene elastomer (SBC), such as large number of post-processing equipment, long process flow, high product haze, opacity, easy clogging of equipment, large footprint, poor operating site environment, wastewater generation, high energy consumption and large investment, etc.
[0007] The purpose of the present invention is to provide a process for devolatilization of lithium-based polymer (SBC) and hydride (HSBC) gels with high melt index, high transparency and low water content. The process is also suitable for devolatilization of low or no melt index polymers. The prepared polymer has a volatile content of ≤0.5% (mass fraction) and has a granular or pelletized appearance, which is convenient for downstream processing and application. The process is simple and low in cost. It can be produced using existing mature equipment and processes and is easy to control and industrialize.
[0008] In order to achieve the above technical objectives, the present invention provides a devolatilization process for a high melt index and high transparency lithium polymer glue solution, which comprises the following steps: sending a dilute glue solution into a falling film evaporation tower for preliminary evaporation, and the gas obtained by evaporation enters a condenser from the top of the falling film evaporation tower for condensation, and the solvent is recovered; the concentrated glue solution obtained by evaporation enters a twin-screw extruder from the bottom of the falling film evaporation tower, and the concentrated glue solution is heated and volatilized in the twin-screw extruder, and the gas obtained by volatilization is sequentially drawn into a front condenser and a rear condenser for condensation, and the solvent is recovered; the polymer melt obtained by volatilizing the solvent is subjected to screw extrusion, pelletizing by an underwater pelletizer, and dehydration by a centrifugal dehydrator to obtain finished glue particles.
[0009] The technical solution of the present invention is to send the dilute glue liquid into the falling film evaporation tower, and distribute it through the distributor arranged at the top of the falling film evaporation tower. Under the action of the distributor, the dilute glue liquid forms a "shower" and is evenly distributed on the semi-circular sieve plate in the falling film evaporation tower to form a thin layer. The falling film evaporation tower is heated by setting a jacket and using steam as a heating medium. The solvent in the dilute glue liquid is evaporated in large quantities. At the same time, the glue liquid with some solvent removed flows to the next semi-circular sieve plate under the action of gravity to further evaporate the solvent. This process is repeated, and the evaporated gas (including solvent gas or The water vapor formed by the water used to terminate the glue liquid) is condensed in the condenser and then the liquid enters the condensation tank until the solid content of the glue liquid reaches the required set amount. The concentrated glue liquid enters the inlet of the twin-screw devolatilization extruder from the bottom of the falling film evaporation tower. The concentrated glue liquid is heated in the twin-screw extruder. The residual solvent in the concentrated glue liquid is forcibly extracted from the gas phase outlet of the twin-screw extruder under a certain temperature and vacuum and enters the front condenser. The condensed solvent enters the front condensation tank, and the uncondensed small amount of solvent or water is sent to the rear condenser by the Roots vacuum pump, and the condensed solvent enters the rear condensation tank. At the same time, the desolvated polymer melt is transported to the finished product silo through twin-screw extrusion, underwater pelletizing, centrifugal dehydration, and vibration screen to obtain pellets.
[0010] The key to the technical solution of the present invention in achieving the devolatilization of high melt index and high transparency lithium polymer glue is to adopt a combined process of falling film evaporation tower pre-concentration and twin-screw machine volatilization. The falling film evaporation tower pre-concentration process can avoid the high melt index polymer glue from sticking and agglomeration, and can perform efficient and continuous pre-concentration on the dilute glue solution. The twin-screw machine can achieve deep devolatilization, and can ensure that the w (total volatile matter) of the extruded sample is less than 0.5%, avoiding the residual solvent from affecting the transparency of the polymer. At the same time, the twin-screw machine has the characteristics of high production capacity.
[0011] As a preferred solution, the falling film evaporation tower is a vertical structure with an aspect ratio of L / D=10-15. A plurality of large semi-circular sieve plates are arranged on the vertical inner wall of the falling film evaporation tower. The distance between the chord center point of the large semi-circular sieve plate and the inner wall of the tower is 1 / 5-1 / 4 of the diameter of the falling film evaporation tower. Any two adjacent large semi-circular sieve plates are evenly arranged in reverse symmetry, and the spacing between any two adjacent large semi-circular sieve plates is 300-350 mm. It is worth further explaining that the falling film evaporation tower adopts a multi-layer sieve plate structure. Under the action of gravity, the glue liquid forms a thin layer on the sieve plate from top to bottom and gradually evaporates without the solvent boiling. The glue liquid gradually concentrates during the flow from top to bottom, has a short residence time, does not overheat, and avoids the glue liquid from forming gel in an overly long time and overheated state. In addition, the glue liquid concentration using the falling film evaporation tower can also be continuous, which is beneficial to large-scale production and operation.
[0012] As a preferred solution, the semi-circular sieve plate has sieve holes of Φ=7-12 mm evenly distributed, and the center distance between any two adjacent sieve holes is 16-24 mm.
[0013] As a preferred solution, the thin rubber liquid is fed into the top of the falling film evaporation tower, and after being evenly distributed by the distributor, it is evenly distributed on the first layer of semi-circular sieve plates to form a film layer. Under the action of heating and gravity, the solvent in the film layer evaporates, and the thin rubber liquid with part of the evaporated solvent flows to the next layer of semi-circular sieve plates to continue evaporating, and so on, and the solid content of the concentrated rubber liquid entering the twin-screw extruder is controlled to be 45-55%. If the solid content of the concentrated rubber liquid is too low, the processing load of the subsequent twin-screw extruder is too large, and the vacuum extraction solvent and condensation recovery efficiency are low; if the solid content of the concentrated rubber liquid is too high or the melt conveying temperature is too low, the melt flow performance is poor, the conveying is difficult, and it is not easy to enter the twin-screw devolatilization extruder.
[0014] As a preferred solution, the solid content of the dilute glue is 8-14%. The solvent used for the general anionic polymer glue is cyclohexane (boiling point 80°C, and azeotropic with water). If the traditional intermittent kettle evaporation concentration is adopted, the efficiency is low, and the polymer on the kettle wall or the surface of the heating coil heated by the jacket is heated first and for a long time, resulting in thermal polymerization of the double bonds in the polymer molecules to produce crosslinking and gel; it is also not conducive to the continuous method for dry devolatilization.
[0015] As a preferred solution, the steam pressure in the falling film evaporation tower is 1-2 bar, the temperature is 80-90° C., and the operating pressure in the falling film evaporation tower is normal pressure.
[0016] As a preferred solution, the total length-to-diameter ratio of the screw of the twin-screw extruder is L / D=42~58, and the extrusion chamber is divided into 9 sections from the inlet to the die; among them, the screw length-to-diameter ratio of the first section is L / D=10~12, the screw length-to-diameter ratios of the second, third, fourth, fifth, sixth, seventh and eighth sections are all L / D=4~5, and gas phase outlets are provided in the fourth, fifth, sixth, seventh and eighth sections.
[0017] As a preferred solution, the parameters of the twin-screw extruder are controlled as follows: die pressure 3.0-5.0 MPa, die temperature 160-185°C, temperature distribution of each section from low to high, temperature range of each section 80-185°C, extruder speed 90-150 r / min, melt residence time 3-5 min. The preferred parameter control can ensure that w (total volatile matter) of the extruded sample is less than 0.5%.
[0018] As a preferred solution, the gas volatilized by heat in the twin-screw extruder is extracted by a Roots vacuum machine and sequentially enters the front condenser and the rear condenser for condensation, and the vacuum degree in the extrusion chamber of the twin-screw extruder is -0.3 to -0.5 bar. If the vacuum degree is too high, the solvent is not easy to be condensed and recovered from the condenser. The Roots vacuum machine is selected to absorb the small amount of solvent gas removed from the twin-screw extruder, which will not cause damage to the Roots vacuum machine, while the use of a common vacuum pump to suck gas and a small amount of water will cause damage to the vacuum pump piston.
[0019] As a preferred solution, the heat transfer medium used by the front condenser and the rear condenser is industrial water at 5-20°C. The condenser and the rear condenser are operated under normal pressure. The front condenser and the rear condenser are respectively equipped with a condensation tank. The condenser and the condensation tank are both well-known equipment to people in the chemical industry.
[0020] The cooling water used by the underwater pelletizer of the present invention is reused through a circulation system, and the recovered solvent is sent to a polymerization unit for cyclic use.
[0021] The falling film evaporation tower of the present invention adopts jacketed steam for heating.
[0022] The twin-screw extruder of the present invention is derived from the continuous horizontal devolatilization extruder of Jiangsu Chengmeng Equipment Co., Ltd.
[0023] The twin-screw heating method of the present invention is electric heating.
[0024] The underwater pelletizer, colloidal pellet centrifugal dehydrator, vibrating screen, finished product silo and water circulation system of the present invention are all well-known equipment to people in the chemical industry.
[0025] Compared with the existing wet devolatilization technology, the technical solution of the present invention brings the following beneficial effects:
[0026] Compared with the existing wet devolatilization technology, the dry devolatilization equipment and process of the present invention have the advantages of less post-processing equipment, shorter process flow, smaller floor space, less likely to clog equipment and pipelines, better operating environment, no need for barrier agents (calcium stearate and other inorganic powders) for underwater pelletizing, no wastewater generation, low energy consumption, small investment, transparent products, and pelletizing water content less than 0.5%. Except for the falling film evaporation tower and the twin-screw extruder, large equipment such as large-scale wet extrusion dehydration machine (SDU), drying box and glue liquid water vapor condensation system are not required. In addition, the dry devolatilization pellets are more beneficial for blending with polyolefin resins; the recovered solvent has a water content of <20mg / Kg, and the solvent recovery rate is >97%, and can be directly used as a polymerization solvent, saving energy consumption.
[0027] The falling film evaporation-twin screw extrusion combined devolatilization process of the present invention has the advantages of good operation flexibility, high processing capacity and efficiency, and is easy to control and adjust.
[0028] Except for the falling film evaporation tower and the twin-screw extruder which need to be specially designed, the other equipments are common equipments in the chemical industry, which generally shows that the equipments are not complicated, can be designed by using the existing experience, and are easy to industrialize. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is the falling film evaporation-twin screw extrusion combined dry devolatilization process of the present invention.
[0030] Figure 2 It is an existing dual-machine dry devolatilization process. DETAILED DESCRIPTION
[0031] The present invention is further described in detail with the following specific examples, which do not constitute limitations on the protection scope of the claims or the implementation methods of the present invention.
[0032] The volatile matter content of rubber is determined according to GB2958-82.
[0033] The Mooney viscosity is measured according to GB / T 1232-1992.
[0034] The devolatilization process of the high melt index and high transparency lithium polymer glue of the present invention is as follows: Figure 1 .
[0035] The devolatilization process of the present invention mainly includes a falling film evaporation unit and a granulation unit. The falling film evaporation unit is mainly composed of a falling film evaporation tower, a condenser and a condensation tank; the granulation unit includes a twin-screw extruder, an underwater pelletizer, a colloidal pellet centrifugal dehydrator, a vibrating screen, a finished product silo and a water circulation system, etc. The twin-screw extruder is also provided with a solvent recovery component, including a front condenser, a front condensation tank, a vacuum pump, a rear condenser and a rear condensation tank, etc.
[0036] The specific devolatilization process of the high melt index and high transparency lithium polymer glue of the present invention is as follows: the dilute glue is sent from the top of the falling film evaporation tower into the falling film evaporation tower, and is distributed through the glue distributor under pressure to form a "shower" and evenly distributed on the first layer of semi-circular sieve plates in the falling film evaporation tower to form a thin layer. The falling film evaporation tower is heated by jacket steam, so that the solvent in the glue is evaporated in large quantities. At the same time, the glue flows to the next layer of semi-circular sieve plates under the action of gravity to continue solvent evaporation, and this cycle is repeated, and the evaporated solvent gas or the water content of the glue is formed when the glue is terminated. The water vapor is output from the top of the falling film evaporation tower, and after condensation in the condenser, the liquid is recovered and enters the condensation tank until the solid content of the glue liquid reaches the required set amount, and the concentrated glue liquid enters the inlet of the twin-screw extruder from the bottom of the falling film evaporation tower. The concentrated glue liquid evaporates under the heat in the extrusion chamber of the twin-screw extruder. The evaporated solvent is forcibly extracted from the gas phase outlet of the twin-screw extruder by the vacuum pump and first enters the front condenser. The condensed solvent is recovered and enters the front condensation tank. The uncondensed small amount of solvent or water is sent to the rear condenser by the Roots vacuum pump, and the condensed solvent is recovered and enters the rear condensation tank. The polymer melt after devolatilization is transported to the finished product silo through twin-screw extrusion, underwater pelletizing, centrifugal dehydration, and vibration screen to obtain polymer glue particles.
[0037] Example 1
[0038] Selection Figure 1 The lithium polymer dry devolatilization process was used to devolatilize the polystyrene-isoprene block copolymer SIS-1106 with a mass fraction of 14.6%. The SIS-1106 rubber solution containing cyclohexane solvent came from the SIS workshop of the synthetic rubber plant of Sinopec Baling Petrochemical Company.
[0039] Among them, the selected falling film evaporation tower has an inner diameter of 0.4m and a height of 4.0m, with an external jacket steam heating. The chord center point of the sieve plate is 80mm away from the falling film evaporation tower wall; the diameter of the sieve holes on the sieve plate is Φ7mm, the spacing between the holes is 16mm, and the spacing between the upper and lower sieve plates is 300mm.
[0040] The twin-screw devolatilizer selected is the TSD-65 devolatilizer manufactured by Jiangsu Chengmeng Equipment Co., Ltd., with a main motor of 55kw, a maximum output speed of 300rpm, a screw outer diameter of Φ61.5mm, a barrel inner diameter of φ=62mm, a screw aspect ratio L / D=42, and a barrel composed of 8 sections connected in series, including 5 sections of vacuum exhaust barrels.
[0041] The heat transfer area of the condenser used for solvent recovery is 4m 2 Other equipment are designed and manufactured according to standards.
[0042] First, the falling film evaporation tower was preheated with 1.4 bar steam for 20 minutes, and then a screw pump was used to deliver a volume flow rate of 950 L / h of the rubber solution to the distributor at the top of the falling film evaporation tower. The pressure in the tower was maintained at atmospheric pressure and the temperature was 85°C. The residence time of the rubber solution was 22 minutes. The evaporated cyclohexane gas was recovered by entering the condenser from the top of the tower. The concentration of the pre-concentrated rubber melt entering the twin-screw inlet from the bottom of the tower was 51.8% (mass fraction).
[0043] The TSD-65 devolatilizer uses an electric heating and temperature control system to control the temperature of each zone. The temperatures of the feed port, zones 1, 2, 3, 4, 5, 6, 7, 8 and the die are set to 80°C, 90°C, 100°C, 115°C, 130°C, 145°C, 160°C, 165°C, 170°C and 180°C, respectively. Zones 4, 5, 6, 7 and 8 are each provided with five gas phase outlets, the screw speed is 180rpm, the melt residence time is 180S, and the die pressure is 4.0MPa; the suction vacuum of the Roots aspirator is -0.38bar; the heat transfer area of each condenser is 4m 2 , 20℃ circulating water is used for cooling; the underwater pelletizer uses 20℃ circulating water to cool the melt pellets.
[0044] As a result, the prepared SIS-1106 elastomer had the appearance of transparent flat pellets, the volatile matter was measured to be 0.42% (by weight), the melt index was 14.63g / 10min; the yield was 124.8kg / h, the recovery rate of cyclohexane was 98.4%, and the water content was 18.5mg / Kg.
[0045] Example 2
[0046] The equipment and process conditions in Implementation 1 remain unchanged, except that SBS-805 glue liquid with a mass fraction of 12.4% of dry glue in cyclohexane (wherein the filling dry glue mass fraction is 34% of cyclohexane oil KN4010) is used. The glue liquid comes from the SBS workshop of the synthetic rubber plant of Sinopec Baling Petrochemical Company, and the flow rate of SBS-805 glue liquid entering the top of the falling film evaporation tower is 750L / h.
[0047] As a result, the melt concentration of the pre-concentrated rubber entering the twin-screw inlet from the bottom of the tower was 53.2% (mass fraction); the die head pressure was 4.0MPa, and the prepared SBS-805 oil-extended rubber had a transparent granular appearance, the volatile matter was measured to be 0.49% (weight), the melt index was 2.87g / 10min, and the yield was 123.7kg / h; the recovery rate of cyclohexane was 97.6%, and the water content was 18.5mg / Kg.
[0048] Example 3
[0049] The equipment and process conditions in Implementation 1 remain unchanged, except that SBS-788 glue solution with a mass fraction of 16.7% of dry glue in cyclohexane is used. The glue solution comes from the SBS workshop of the synthetic rubber plant of Sinopec Baling Petrochemical Company. The flow rate of the glue solution entering the top of the falling film evaporator is 950L / h, and the screw speed is 210rpm.
[0050] As a result, the concentration of the pre-concentrated rubber melt entering the twin-screw inlet from the bottom of the tower was 55.8% (mass fraction), the die head pressure was 4.2MPa, and the prepared SBS-788 elastomer had a transparent granular appearance. The volatile matter was measured to be 0.38% (weight), the melt index was 10.63g / 10min, and the productivity was 139.8kg / h; the recovery rate of cyclohexane was 97.2%, and the water content was 18.4mg / Kg.
[0051] Comparative Example 1
[0052] The SIS-1106 glue solution and TSD-65 devolatilizer and related process conditions in Example 1 remain unchanged, only the falling film evaporation tower pre-concentration unit is replaced with an SCP devolatilizer (concentrator). The inner diameter of the barrel is 320mm, the barrel is a double-layer design, steam is passed inside, the barrel is composed of 2 barrels in series, the length-to-diameter ratio L / D=7:1, and the internal dual-rotor speed is set. The dual rotors rotate in the same direction with differential speed. The speed is controlled by a frequency converter, and the maximum speed is 50rpm. There are 2 vacuum exhaust chambers on the barrel, which are connected to the vacuum condensation system through vacuum pipes and valves. See the process for dual-machine equipment Figure 2 The entire equipment was manufactured by Jiangsu Chengmeng Equipment Co., Ltd. and assembled in the synthetic rubber plant of Sinopec Baling Petrochemical Company.
[0053] The results showed that the die head pressure of the TSD deep devolatilization twin-screw pelletizer unit was only 1.6MPa, the output of SIS-1106 transparent pellets was 60.2kg / h, the maximum feed rate of SIS-1106 glue solution to the SCP devolatilization reaction concentrator was 468L / h, the highest concentration of the glue solution was 32.8% (weight), the maximum output or feed rate to the TSD unit was 199.5L / h; the solvent recovery rate was 91.4%.
Claims
1. A devolatilization process for a high melt index and high transparency lithium polymer glue, characterized in that: The dilute rubber liquid is sent to the falling film evaporation tower for preliminary evaporation, and the gas obtained by evaporation enters the condenser from the top of the falling film evaporation tower for condensation, and the solvent is recovered; the concentrated rubber liquid obtained by evaporation enters the twin-screw extruder from the bottom of the falling film evaporation tower, and the concentrated rubber liquid is heated and volatilized in the twin-screw extruder, and the volatilized gas is successively drawn into the front condenser and the rear condenser for condensation, and the solvent is recovered; the polymer melt obtained by volatilizing the solvent is screw extruded, pelletized by an underwater pelletizer and dehydrated by a centrifugal dehydrator to obtain finished rubber particles.
2. The devolatilization process of a high melt index and high transparency lithium polymer glue according to claim 1, characterized in that: The falling film evaporation tower is a vertical structure with an aspect ratio of L / D=10-15. A plurality of semi-circular sieve plates are arranged on the vertical inner wall of the falling film evaporation tower. The distance between the chord center point of the semi-circular sieve plate and the inner wall of the tower is 1 / 5-1 / 4 of the diameter of the falling film evaporation tower. Any two adjacent semi-circular sieve plates are evenly arranged in reverse symmetry, and the spacing between any two adjacent semi-circular sieve plates is 300-350 mm.
3. The devolatilization process of a high melt index and high transparency lithium polymer glue according to claim 2, characterized in that: The semi-circular sieve plate is evenly distributed with sieve holes of Φ=7-12 mm, and the center distance between any two adjacent sieve holes is 16-24 mm.
4. The devolatilization process of a high melt index and high transparency lithium polymer glue according to any one of claims 1 to 3, characterized in that: The dilute rubber liquid is fed into the top of the falling film evaporation tower, and after being evenly distributed by the distributor, it is evenly distributed on the first layer of semi-circular sieve plates to form a film layer. Under the action of heating and gravity, the solvent in the film layer evaporates, and at the same time, the dilute rubber liquid with part of the evaporated solvent flows to the next layer of semi-circular sieve plates to continue evaporating, and this cycle is repeated to control the solid content of the concentrated rubber liquid entering the twin-screw extruder to be 45-55%.
5. The devolatilization process of a high melt index and high transparency lithium polymer glue according to claim 4, characterized in that: The solid content of the dilute glue solution is 8-14%.
6. The devolatilization process of a high melt index and high transparency lithium polymer glue according to claim 4, characterized in that: The steam pressure in the falling film evaporation tower is 1-2 bar, the temperature is 80-90° C., and the operating pressure in the falling film evaporation tower is normal pressure.
7. The devolatilization process of a high melt index and high transparency lithium polymer glue according to claim 1, characterized in that: The total screw length-to-diameter ratio of the twin-screw extruder is L / D=42-58, and the extrusion chamber is divided into 9 sections from the inlet to the die; among them, the screw length-to-diameter ratio of the first section is L / D=10-12, the screw length-to-diameter ratios of the second, third, fourth, fifth, sixth, seventh, and eighth sections are all L / D=4-5, and gas phase outlets are provided in the fourth, fifth, sixth, seventh, and eighth sections.
8. The devolatilization process of a high melt index and high transparency lithium polymer glue according to claim 1, characterized in that: The parameters of the twin-screw extruder are controlled as follows: die pressure 3.0-5.0 MPa, die temperature 160-185°C, temperature distribution of each section from low to high, temperature range of each section 80-185°C, extruder speed 90-150 r / min, melt residence time 3-5 min.
9. The devolatilization process of a high melt index and high transparency lithium polymer glue according to claim 1, characterized in that: The gas volatilized by heat in the twin-screw extruder is extracted by a Roots vacuum machine and sequentially enters the front condenser and the rear condenser for condensation. The vacuum degree in the extrusion chamber of the twin-screw extruder is -0.3 to -0.5 bar.
10. The devolatilization process of a high melt index and high transparency lithium polymer glue according to claim 1, characterized in that: The heat transfer medium used by the front condenser and the rear condenser is industrial water at 5-20°C.
Citation Information
Patent Citations
Preparation process of styrene type polybasic copolymerized high molecular material
CN106188400A
Polymer solution devolatilization method and device
CN115572337A
Method for removal of volatile component from polymer solution
CN1214341A
Manufacturing process of block copolymer
JP2005060536A
